2002
DOI: 10.1086/323947
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of the First Stars. I. The Primordial Star‐forming Cloud

Abstract: To constrain the nature of the very first stars, we investigate the collapse and fragmentation of primordial, metal-free gas clouds. We explore the physics of primordial star formation by means of threedimensional simulations of the dark matter and gas components, using smoothed particle hydrodynamics, under a wide range of initial conditions, including the initial spin, the total mass of the halo, the redshift of virialization, the power spectrum of the DM fluctuations, the presence of HD cooling, and the num… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
1,146
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,035 publications
(1,213 citation statements)
references
References 67 publications
49
1,146
2
3
Order By: Relevance
“…Simulations of the collapse of primordial molecular clouds (Bromm et al, 1999(Bromm et al, , 2002Abel et al, 2000;Yoshida et al, 2006;Gao et al, 2007) suggest that the first generation of stars contained many 'very massive stars' (VMSs) with m > 100 M . This is because of the slow subsonic contraction -a regime set up by the main gas coolant, molecular hydrogen -further fragmentation into sub-components is not seen (although it is not clear if this is a numerical effect, rather than due to the gas physics, see Glover et al, 2008).…”
Section: Population III Remnantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations of the collapse of primordial molecular clouds (Bromm et al, 1999(Bromm et al, , 2002Abel et al, 2000;Yoshida et al, 2006;Gao et al, 2007) suggest that the first generation of stars contained many 'very massive stars' (VMSs) with m > 100 M . This is because of the slow subsonic contraction -a regime set up by the main gas coolant, molecular hydrogen -further fragmentation into sub-components is not seen (although it is not clear if this is a numerical effect, rather than due to the gas physics, see Glover et al, 2008).…”
Section: Population III Remnantsmentioning
confidence: 99%
“…If star formation proceeds in small mini-halos (T vir < 10 4 K), triggered by H 2 cooling (Bromm et al, 1999(Bromm et al, , 2002Abel et al, 2000), then by the time more massive halos are built-up, they will have been enriched with some traces of metals, brought in by their progenitors. Fragmentation and formation of low mass stars starts as soon as gas is polluted by metals created in the first PopIII stars (Omukai et al, 2008).…”
Section: Stellar-dynamical Processesmentioning
confidence: 99%
“…The formation of the first stars marked the end of the cosmic Dark Ages and began the transformation of the universe from a cold, dark featureless void into the hot, transparent cosmic web of galaxies we observe today (Abel et al 2002;Bromm et al 2002;Whalen et al 2004;Kitayama et al 2004;Alvarez et al 2006;Abel et al 2007). Population III (or Pop III) stars were also the first great nucleosynthetic engines of the universe, expelling large quantities of the heavy EACOA Fellow, E-mail: ken.chen@nao.ac.jp elements needed for the later formation of planets and life (e.g., Bromm et al 2003;Kitayama & Yoshida 2005;Greif et al 2007;Karlsson et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One potential pathway is the collapse of a primordial, i.e., metal-free, "normal" star into a stellar-mass black hole. Earlier numerical simulations performed to study the formation of the first generation of stars (Abel et al 2002;Bromm et al 2002; ⋆ Corresponding author: latif@iap.fr Yoshida et al 2006) suggested that the masses of the first stars are of the order of a few hundred solar. However, recent simulations found that the protostellar disk forming in the minihalo fragments into multiple clumps (Clark et al 2011;Greif et al 2012;Stacy et al 2012;Latif et al 2013b; and leads to the formation of multiple stars.…”
Section: Introductionmentioning
confidence: 99%